1992
DOI: 10.1073/pnas.89.10.4744
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of human methyl-directed DNA methyltransferase and the fidelity of cytosine methylation.

Abstract: The properties of the methyl-iected DNA (cytosine-5-)-methyltransferase (EC 2.1.1.37) suggest that it is the enzyme that ntains patterns of methylation in the human genome. Proposals for the enzyme's mhanism of action suggest that 5-methyldeoxycytidine is produced from deoxycytidine via a dihydrocytosine intermediate. We have used an oligodeoxynuceotide containg 5-fluorodeoxycytidine as a suicide substrate to capture the enzyme and the dihydrocytosine intermediate. Gel retardation experiments demonstrate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 28 publications
4
82
0
Order By: Relevance
“…Structural studies with bacterial cytosine methylases have shown that the cytosine base is extruded from the DNA double helix into the active site of the enzyme where it can be reacted upon without steric hindrance (23). The active site cysteine attacks the 6-position of the pyrimidine ring and then activates the 5-carbon for nucleophilic attack of the methyl group donor S-adenosyl-L-methionine (AdoMet) (24).…”
mentioning
confidence: 99%
“…Structural studies with bacterial cytosine methylases have shown that the cytosine base is extruded from the DNA double helix into the active site of the enzyme where it can be reacted upon without steric hindrance (23). The active site cysteine attacks the 6-position of the pyrimidine ring and then activates the 5-carbon for nucleophilic attack of the methyl group donor S-adenosyl-L-methionine (AdoMet) (24).…”
mentioning
confidence: 99%
“…They have well characterized DNA sequence specificities (11) and they form abortive covalent complexes (Fig. 1) between an active-site cysteine and 5-fluorocytosine in their DNA recognition sequences (12)(13)(14)(15). In this report, we demonstrate this approach to macromolecular assembly using two representative methyltransferases: M⅐HhaI and M⅐MspI.…”
mentioning
confidence: 99%
“…NaCl (50 mM) was used when both were incubated together. The products were separated on native protein gels poured with an exponential gradient (6-20% arcylamide) and run at 25 mA for 3 hr (14). The gel was then exposed to x-ray film directly for autoradiography.…”
Section: Molecular Cloning Of the M⅐hhai-dod Fusion Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation of cytosine is catalyzed by DNA methyltransferase enzymes, all of which work through the same catalytic mechanism (2). The addition of a methyl group at the 5-position of cytosine is dependent on formation of a covalent intermediate between a conserved cysteine moiety of the enzyme and the 6-position of the cytosine ring ( Figure 1A&B) (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%